Konsep Taqdir dalam al-Qur’an (Analisis Semantik Toshihiko Izutsu) - Dame Harahap; Bahrudin Zamawi (PT. Student Rihlah Indonesia, 2025)
This research is motivated by the gap in meaning between the understanding of the Qur'an and the fatalistic views of society in comprehending taqdir (divine destiny). This is caused by a resigned attitude of giving up without effort that has become a cultural norm among people when faced with various life problems, such as poverty, calamities, and so on. In contrast, the Qur'an implicitly emphasizes the concept of effort in human life. This research aims to analyze the concept of taqdir in the Qur'an using Toshihiko Izutsu's Qur'anic semantic perspective. This research is a literature review that utilizes data from the Qur'an and books by Toshihiko Izutsu. Generally, this research is categorized as qualitative research. In terms of its procedure, this study is descriptive, and within the field of Qur'anic studies, it falls under the thematic term interpretation method. Through this research, it was found from the weltanschauung (worldview) of the Qur'an, as viewed through Izutsu's semantics, that taqdir does not restrict human life. This is because taqdir is not merely certain but also measurable, in which the measure that Allah sets in human taqdir takes the form of ability or a burden of responsibility (taklif), allowing humans to determine their life's direction.